2015
DOI: 10.1039/c5ta01296a
|View full text |Cite
|
Sign up to set email alerts
|

Carbides of group IVA, VA and VIA transition metals as alternative HER and ORR catalysts and support materials

Abstract: Nano-carbides were synthesized and tested as catalysts and supports for hydrogen evolution reaction (HER) and oxygen reduction reaction (ORR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(106 citation statements)
references
References 31 publications
4
99
1
2
Order By: Relevance
“…The β‐Mo 2 C exhibited distinct HER activity, the overpotential with current density of 10 mA cm −2 is about 387 mV. The remarkably low HER performance was consistent with the reported one in previous work where the β‐Mo 2 C catalyst was also prepared by molten salt method . The large size and the dense surface of Mo 2 C particles should be responsible for this performance.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The β‐Mo 2 C exhibited distinct HER activity, the overpotential with current density of 10 mA cm −2 is about 387 mV. The remarkably low HER performance was consistent with the reported one in previous work where the β‐Mo 2 C catalyst was also prepared by molten salt method . The large size and the dense surface of Mo 2 C particles should be responsible for this performance.…”
Section: Resultssupporting
confidence: 88%
“…The remarkably low HER performance was consistent with the reported one in previous work where the β-Mo 2 C catalyst was also prepared by molten salt method. [40] The large size and the dense surface of Mo 2 C particles should be responsible for this performance. As compared to β-Mo 2 C, NiO/β-Mo 2 C exhibited relatively lower HER activity, the overpotential with a current density of 10 mA cm À 2 is about 483 mV, which is larger than that of β-Mo 2 C by 96 mV.…”
Section: Catalysts Preparation and Characterizationmentioning
confidence: 99%
“…Regmi et al 42 . compared the electroactivity of 9 TMCs for HER, and found that Mo2C catalyst had significantly higher activity than others, followed by WC and V8C7 in order.…”
Section: Transition Metal Carbidesmentioning
confidence: 99%
“…[10] In 2011, Shen and co-workers first took advantage of the platinum-like feature of V 8 C 7 to reduce the usage of Pt. Specially, they concluded that Mo 2 C, WC, and V 8 C 7 deliver particularly enhanced HER activity compared with others.…”
mentioning
confidence: 99%